The forgetting spell a wishing day novel - Myracle, Lauren 1969- (Katherine Tegen Books, an imprint of HarperCollins Publishers, 2017)
Most people in Willow Hill think Darya is the prickliest of the Blok sisters. What they don't realize is that on the inside, Darya is soft and gooey from feeling everything, all the time. When Darya turns thirteen, the goo gets stickier ... and as Darya's Wishing Day approaches, all she wants is to forget the silly tradition ever existed. Except... she can't. Ten years ago, a wish made by Darya's mother splintered their family into pieces. Last year, Darya's sister Natasha wished for their broken mother to return. This year, Darya has a chance to wish away parts of the past, and who wouldn't want to do that? Darya, that's who! The past is something you're supposed to leave behind. Which is why Darya has locked and sealed her most painful memories inside the far corners of her mind, where they can no longer hurt her. But when some of them begin to leak out, Darya realizes the decision about what to wish for ... and what not to wish for ... is probably the most important choice of her life
Keywords: Fantasy fiction / fast / (OCoLC)fst01726607; Fiction / fast / (OCoLC)fst01423787; Juvenile works / fast / (OCoLC)fst01411637; Fantasy fiction / lcgft; Dysfunctional families / fast / (OCoLC)fst01728523; Magic / fast / (OCoLC)fst01005468; Memory / fast / (OCoLC)fst01015913; Sisters / fast / (OCoLC)fst01119758; Wishes / fast / (OCoLC)fst01176272; Dysfunctional families -- Juvenile fiction; Sisters -- Juvenile fiction; Wishes -- Juvenile fiction; Memory -- Juvenile fiction; Magic -- Juvenile fiction; Sisters; Wishes; Magic; Families; Fantasy fiction; Dysfunctional families; Memory; Fantastischer Roman; Kinderbuch; Jugendbuch